Effects of Nitrogen and Phosphorus on Botanical Composition, Yield and Nutritive Value of Rangelands - TURK, MEVLUT; CELIK, NECMETTIN; BAYRAM, GAMZE; BUDAKLI, EMINE (Asian Journal of Chemistry, 2010)
This works report the effects of nitrogen and phosphorus on botanical composition, yield and quality of rangelands in Bursa area between 2001 and 2003. The research was set up as randomized complete block design with three replications starting in November-2001. Four different N doses (0, 50, 100 and 150 kg ha-1) and three different P doses (0, 50 and 100 kg ha-1) were applied and their effects on rangeland were investigated. Ammonium nitrate and triple super phosphate were used as nitrogenous and phosphorous fertilizers. All of the phosphorous fertilizer and 50 % of the nitrogenous fertilizer were applied in Fall and the remaining N fertilizer was applied in Spring. Effects of fertilizer applications on botanical composition, dry matter yield, crude protein concentration and crude protein yield were investigated. The results were analyzed to determine the most cost effective fertilizer doses. The average for over two years, nitrogen applications increased grass dry weight ratios, while it decreased legumes'dry weight ratios. The highest dry matter and crude protein yield was obtained from 100 kg ha-1 P + 150 kg ha-1 N treatments, while the lowest values was obtained from control plots. The economic optimum was determined in the highest fertilizer doses 100 kg ha-1 P + 150 kg ha-1 N producing 9.85 t ha-1 forage dry matter with a crude protein concentration of 120 g kg-1 and legume proportion of 9.72 %.